2017
DOI: 10.1016/j.livsci.2017.02.016
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between water buffalo cow temperament and milk yield and quality traits

Abstract: The aims of this study were to assess the relationship between reactivity during milking and daily distances traveled by lactating water buffalo cows and to assess the association of these behavioral traits with milk yield and quality traits. Reactivity during milking was measured as a 4-point milking reactivity score (MRS, N=114 cows) where 1=stands quietly, 2=slight hind leg movements, 3=vigorous hind leg movements, and 4=continual vigorous hind leg movements or the stockperson ties the animal. Cows were cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 36 publications
3
13
0
4
Order By: Relevance
“…However, in some published papers there was no available information about relationship between the temperament score and somatic cell count in milk. Some authors found relationship between these traits in cattle and buffalo, more temperamental animals have higher somatic cell counts (Orbán et al, 2011;Carvalhal et al, 2017). Hypothesis of this study was that the more temperamental animals have higher somatic cell count in milk during the whole lactation period compared to the calmer ones.…”
Section: Introductionmentioning
confidence: 74%
“…However, in some published papers there was no available information about relationship between the temperament score and somatic cell count in milk. Some authors found relationship between these traits in cattle and buffalo, more temperamental animals have higher somatic cell counts (Orbán et al, 2011;Carvalhal et al, 2017). Hypothesis of this study was that the more temperamental animals have higher somatic cell count in milk during the whole lactation period compared to the calmer ones.…”
Section: Introductionmentioning
confidence: 74%
“…Em bubalinos, os teores de lactose apresentam valores entre 4,8 e 5,5%. O leite de búfala contém elevado teor de sólidos totais, essencialmente a gordura, constituinte importante para a produção de derivados (CARVALHAL et al 2017).…”
Section: Leite Bubalinounclassified
“…Considerando o aspecto comportamental, búfalas leiteiras têm necessidade de expressar seus comportamentos naturais, como poder percorrer longas distâncias durante o dia, necessidade que está diretamente ligada à disponibilidade de espaço. Carvalhal et al (2017) observaram que búfalas leiteiras percorreram diariamente, em média, 7413 ± 1039 m/dia (média ± desvio padrão), variando de 5762 a 10124 m/dia, mostrando a relevância do comportamento exploratório para essa espécie. O resultado encontrado por esses autores foi superior à distância média percorrida relatada por Sabia et al (2014) (2,1 ± 0,3 km por dia).…”
Section: Boa Interação Humano-animalunclassified
“…O resultado encontrado por esses autores foi superior à distância média percorrida relatada por Sabia et al (2014) (2,1 ± 0,3 km por dia). Além desses achados, Carvalhal et al (2017) não encontraram relações significativas entre a distância média percorrida por dia e a produção e a qualidade (gordura e proteína) do leite de búfalas, indicando que essa atividade exploratória não afeta os índices produtivos desses animais.…”
Section: Boa Interação Humano-animalunclassified